PENGARUH KOMITMEN ORGANISASIONAL DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MODERASI BUDAYA ORGANISASI (Studi pada Dinas Kesehatan Kabupaten Temanggung) - Agus Munadi, 11.5202.0005 (Students Journal of Economic and Management, 2013)
Human resources in development  administering government and moreover have in health development dominant factor. Many factors that affect employees performance among other factors employees in terms of the ability  organizational commitmen, job characteristic   and cultural factors organization surrounding in the organization. The problems are examined in research is: (1) how influence organizational commitmen on performance to civil servants?, (2) how influence job characteristics on  performance?. (3) what influence organizational commitment to performance by moderation cultural organization, (4) how job characteristics influence on performance by employees cultural organization with moderation cultural organization. Samples research is Health Service Employee Temanggung District of Central Java about 115 people with the purposive sampling techniques. A test, regression analysis the T, the F, and coefficients determination.Th e results showed the organizational commitment (X 1) have a positive influence on performance (Y). Job characteristics (X2) have a positive influence on performance (Y). Of the two independent variables,. organizational commitment (X1) and job characteristics (X2) turned out to be the most dominant influence on performance is variable (x2) job characteristics. The results of the variable oraganisasional with the commitment to moderation organizational culture organizational culture affect variables negative or weakens against the performance of employees. The results of the job characteristics with moderation organizational culture organizational culture affect variables show negative or weakens against performance. Keywords: organizational Commitment, job characteristics, organizational culture, and performance.